John Wayne - Wayne, John, 1907-1979.; Bradbury, Robert N. (Robert North); Whitman, Phil.; Pierson, Carl.; Beebe, Ford I. (La Crosse, Wis. : Platinum Disc Corp., 2004)
"Rainbow valley: John Martin, a covert government, is sent to protect the men building a road in Rainbow Valley, from the gang who claims the territory and whose main interest lies in the area's gold mines. And when the gang plans to engage in illegal activity by blowing up the road with dynamite. Martin realizes he must put a stop to the gang for good."--Container.
"His private secretary: Dick Wallace is a young man with little on his mind other than women, women, and more women. His father, a driven businessman, is tired of his son's leisurely ways and puts him to work as his company's collection manager. Dick travels to the neighboring town of Somerville to track down a debtor for payment but is quickly distracted by Marion, the man's pretty granddaughter. Dick attempts Don Juanesque charm, but ends up coming off crudely, and he is rebuked with a slap from Marion. But this western Romeo has been bitten by the love bug and will not be rejected so easily. In a favorable twist of fate for Dick, Marion goes to work for the elder Wallace as his secretary. Now if Dick wants Marion to return his love, he must prove sincerity and show her that's he's not the irreverent playboy of the past."-- Container.
"Paradise Canyon: John Wyatt, a covert government agent, is on the hunt for a band of counterfeiters believed to be involved with a traveling medicine show run by Doc Carter. Wyatt suspects Doc as being the ringleader, but when he and his daughter Linda are kidnapped, john knows he's been tracking the wrong person. Now the lawman must uncover the truth of who's behind the counterfeiting and disband the group before harm can come to the innocent Carters."-- Container.
"Shadow of the eagle: A mystery pilot, known only as the Eagle, is making treacherous threats in a most unusual way - by writing them in the sky! The creative criminal's intimidation tactics are aimed at a company, which has somehow agitated the mystery man, and now he wants his own type of justice. The word on the street is that Nathan Gregory, a traveling fair owner, is the Eagle's true identity. But when Gregory turns up missing, they begin to doubt that the man disappeared on his own. Deteremined to reveal the truth, pilot Craig McCoy vows to unmask the unknown sky-writer before anything else can run afoul."-- Container.
[Film 1.] Rainbow valley (1935, ca. 45 min.) / directed by Robert North Bradbury -- [Film 2.] His private secretary (1933, ca. 60 min.) / directed by Phil Whitman -- [Film 3.] Paradise canyon (1935, ca. 53 min.) / directed by Carl Pierson -- [Film 4.] Shadow of the eagle (1932, ca. 186 min.) / directed by Ford I. Beebe.
John Wayne.
Not rated.
DVD; digitally mastered; digitally enhanced audio 5.1.
Keywords: Western films; Adventure films; DVDs; DVD-Video disc